Does exercise pulmonary hypertension exist?. Issue 5 (September 2016) - Lau, Edmund M.; Chemla, Denis; Whyte, Kenneth; Kovacs, Gabor; Olschewski, Horst; Herve, Philippe
Abstract : Purpose of review: The exercise definition of pulmonary hypertension using a mean pulmonary artery pressure threshold of greater than 30 mmHg was abandoned following the 4th World Pulmonary Hypertension Symposium in 2008, as this definition was not supported by evidence and healthy individuals frequently exceed this threshold. Meanwhile, the clinical value of exercise pulmonary hemodynamic testing has also been questioned. Recent findings: Recent data support the notion that an abnormal pulmonary hemodynamic response during exercise (or exercise pulmonary hypertension) is associated with symptoms and exercise limitation. Pathophysiologic mechanisms accounting for the development of exercise pulmonary hypertension include increased vascular resistance, excessive elevation in left atrial pressure and/or increased volume of trapped air during exercise, resulting in a steep rise in pulmonary artery pressure relative to cardiac output. Recent evidence suggests that exercise pulmonary hypertension may be defined by a mean pulmonary artery pressure surpassing 30 mmHg together with a simultaneous total pulmonary resistance exceeding 3 WU. Summary: Exercise pulmonary hypertension is a clinically relevant entity and an improved definition has been suggested based on new evidence. Exercise pulmonary hemodynamics may help unmask early or latent disease, particularly in populations that are at high risk for the development of pulmonary hypertension.